1998
DOI: 10.1046/j.1469-0705.1998.12060385.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of choroid plexus cysts, echogenic heart foci and renal pyelectasis in the first trimester

Abstract: Although the majority of aneuploidies were detected by increased nuchal translucency and/or the presence of structural abnormalities (78%; 25/32), the use of soft ultrasonographic markers in the first trimester would have increased the overall detection by a further 3%. These data are preliminary and many thousands of pregnancies will need to be examined to determine the significance of the individual markers in different chromosomal abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The use of soft ultrasound markers (in the first or second trimester) can provide further aid in diagnosing fetuses with Down's Syndrome. We have previously reported that the use of specific markers in the first trimester can increase the detection rate by 3% 21 . Verdin et al 22,23 have reported on the impact of second trimester ultrasound markers, suggesting that such markers can be used to modify the risks of being affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of soft ultrasound markers (in the first or second trimester) can provide further aid in diagnosing fetuses with Down's Syndrome. We have previously reported that the use of specific markers in the first trimester can increase the detection rate by 3% 21 . Verdin et al 22,23 have reported on the impact of second trimester ultrasound markers, suggesting that such markers can be used to modify the risks of being affected.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of nuchal translucency was proposed as an effective alternative screening test for trisomy 21. In a recent multicentre study of nuchal translucency screening in about 100,000 cases the detection rate was reported to be 77% for a false positive rate of 5% 5 .…”
Section: Introductionmentioning
confidence: 99%
“…They are important because of their statistical association with chromosomal abnormalities. In certain studies for example according to Whitlow et al in 1998, soft markers increased the detection rate of aneuploidy in the first trimester by 3% (2). A recent meta-analysis by Agathokleus et al has shown that the LR of isolated EIF in the second trimester (14-24 weeks) for Trisomy 21 is 0.95.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…There is also an increased possibility of detection of these ultrasound soft markers, specially the EIF in the first trimester. A study by Whitlow et al has shown that although majority of aneuploidies were detected by nuchal translucency (NT) and the presence of structural abnormalities, the detection rate increased further by 3% with the usage of ultrasound soft markers in the first trimester (2). Dagklis et al has suggested that the use of soft markers in first trimester can improve the accuracy of screening but has not analyzed its relationship with biochemical screening (3).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the other nonstructural markers that are currently used to assess the risk of aneuploidy in the second trimester may also be visible in the first trimester. Whitlow et al 18 reported the prevalence of 3 markers (choroid cysts, renal pyelectasis, and echogenic intracardiac foci) in 5383 women scanned between 10 and 14 weeks' gestation. In normal fetuses, the prevalence of these markers was 2.2%, 0.9%, and 0.6%, respectively.…”
Section: Nonstructural Sonographic Markersmentioning
confidence: 99%